Bitwise-based Routing Algorithms in Optical Multistage Interconnection Network - Abed, Farzaneh (2007)
Recent advances in electro-optic technologies have made optical communication a promising networking alternative to meet the ever increasing demands of high performance computing communication applications for high channel bandwidth, low communication latency and parallel processing as well. Optical Multistage Interconnection Network (OMIN) is very popular in switching and communication among other types of interconnection networks. A major problem in OMIN is crosstalk, which is caused by coupling two signals within a switching element. Crosstalk problem in a switch is the most prominent factor which reduces the signal-to-noise ratio and restricts the size of network. To avoid crosstalk in OMINs many algorithms have been proposed by many researchers such as the Four Heuristic, Simulated Annealing, Genetic, Remove Last Passes and Zero Algorithms. Under the constraint of avoiding crosstalk, the interests of these algorithms are to find a permutation that uses a minimum number of passes and minimum execution time. Accordingly the objective of this research is to optimize and improve the current algorithms in terms of number of passes and execution time. To achieve such goal, this research follows three approaches. In the first, the Improved Zero algorithm is proposed to solve the problem and secondly, the Bitwise Improved Zero algorithm is developed. Finally Four Heuristic and Difference Increasing and Decreasing routing algorithms based on bitwise operation are established. The results of this study show that Bitwise Improved Zero algorithms reduce the execution time nearly seven times. This reduction is very considerable because the execution time of routing algorithms is very important to route the messages in the networks. Moreover Improved Zero algorithm was shown to be more accurate and efficient compared to other algorithms in terms of the average number of passes and execution time. Furthermore by converting Four Heuristic and Difference Increasing and Decreasing routing algorithms to bitwise algorithms the execution time was improved significantly.